Variation of textural properties in pears dried by different solar methodologies. - Abílio, Sandra (2012)
In Portugal, the variety of S. Bartholomew (Pyrus communis L.) pears are subject to an artisan drying process consisting of direct open-air sun exposure, leading to a traditional product with unique texture characteristics, called “Pêra Passa de Viseu”. However, the drying process does not provide the current standards of safety and, therefore, recent investigations have emerged with alternatives to the traditional drying process. The changes that occur in the pears during the drying process are of the most importance to define the sensory characteristics and the quality of this product. As the texture is a highly valued characteristic for this product, it is necessary to verify that the different drying methods give place to products as similar to the traditional as possible. Thus, this study aimed at determining the changes that occur in the texture with the drying process and compare the texture of pears dried by two different drying processes, namely the traditional open-air and the solar stove with ventilation. Pears of the Portuguese variety S. Bartholomew were obtained from a local producer, both in the fresh state and after drying by the traditional procedure. Some of the fresh pears were dried by the alternative method. From the results obtained, it was possible to observe that both drying processes affected the initial texture. However, no important differences were seen when the two drying methods were compared with each other, thus allowing to conclude that the alternative drying methodology can be used to replace the traditional one, without altering the textural properties of the final product and with an highly added value in food safety.